(untitled) (Bangladesh Journal of Medical Microbiology, 2026)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common causes of hospital-acquired infections and is also a significant contributor to healthcare- and community associated infections worldwide. The increasing resistance due to the presence of resistance genes, coupled with the irrational use of antibiotics, has worsened the clinical situation. This rising antimicrobial resistance highlights the urgent need for the development of an effective vaccine to prevent MRSA infections. Objective: The objective of this study was to identify a specific MRSA protein, on the basis of molecular weight, that induces defensive antibody conformation in serum and splenic cell culture supernatant following immunization with a formalin-inactivated whole-cell MRSA vaccine. Methodology: This was an animal study which was conducted in the Department of Microbiology at Dhaka Medical College, Dhaka, Bangladesh for a period of one year from January 2022 to December 2022. MRSA strains were obtained from various clinical samples and used to prepare a formalin-inactivated whole-cell vaccine. Fifteen Swiss albino mice were immunized intradermally with three boluses of this vaccine. Fourteen days after the third cure, the mice were challenged intradermally with live MRSA and covered for another 14 days. Sera were collected from tail blood, and splenic cell culture supernatants were gathered. The MRSA antigens used in the vaccine were sonicated and separated using SDS- PAGE electrophoresis according to molecular weight. ELISA was used to descry and quantify the antibodies in both serum and splenic cell supernatants that specifically bound to the MRSA antigens. Results: Following MRSA challenge, 100% of the immunized mice survived the 14-day observation period, indicating a strong protective response. ELISA results revealed that both pre- and post-challenge serum samples had significantly higher IgG optical density values compared to the control group. The highest antibody response was observed against the antigen eluted from the SDS-PAGE band corresponding to a molecular weight range of 95–130 kDa, in both serum and splenic cell culture supernatant. Conclusion: Formalin-inactivated intradermal immunization with MRSA generated a strong protective immune response in Swiss albino mice, targeting a specific antigen within the 95 to 130 kDa molecular weight range. This antigen may be a promising candidate for the development of a novel and effective MRSA vaccine. Bangladesh Journal of Medical Microbiology, July 2025;19 (2):136-142